Term Structure Dynamics in Theory and Reality - Dai, Qiang; Singleton, Kenneth (Review of Financial Studies, 2003)
This article is a critical survey of models designed for pricing fixed-income securities and their associated term structures of market yields. Our primary focus is on the interplay between the theoretical specification of dynamic term structure models and their empirical fit to historical changes in the shapes of yield curves. We begin by overviewing the dynamic term structure models that have been fit to treasury or swap yield curves and in which the risk factors follow diffusions, jump-diffusion, or have "switching regimes." Then the goodness-of-fit of these models is assessed relative to their abilities to (i) match linear projections of changes in yields onto the slope of the yield curve; (ii) match the persistence of conditional volatilities, and the shapes of term structures of unconditional volatilities, of yields; and (iii) to reliably price caps, swaptions, and other fixed-income derivatives. For the case of defaultable securities we explore the relative fits to historical yield spreads.